If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(u + -3) + -8u = -12 Reorder the terms: 5(-3 + u) + -8u = -12 (-3 * 5 + u * 5) + -8u = -12 (-15 + 5u) + -8u = -12 Combine like terms: 5u + -8u = -3u -15 + -3u = -12 Solving -15 + -3u = -12 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -3u = -12 + 15 Combine like terms: -15 + 15 = 0 0 + -3u = -12 + 15 -3u = -12 + 15 Combine like terms: -12 + 15 = 3 -3u = 3 Divide each side by '-3'. u = -1 Simplifying u = -1
| 108=LW | | -18n+12=-17n-14 | | A=15*12 | | -3x-10=5x+30 | | (-5xy)(2xy^2)= | | -4x-8=7 | | q/9=7/5 | | 10/7=5w | | 273729=72292 | | 8x^4-8= | | 7x+2y=20000 | | x+106+95=180 | | -14-(-32)=x/5 | | 65=32+6(x-2) | | 7x-2=-2x+1 | | 26x+1=27x-4 | | 159=207-x | | 13x-1+77=180 | | 240-w=85 | | 13x-1=77 | | 2t-1/3+3t-4/5=t | | 3x^3-24x=x | | 40/5x=2 | | 3ln(x-1)+3=9 | | r-1/4=8/9 | | 33-5x+11=3x-69 | | h^2+28h-31=0 | | 6x-3=2x+21 | | y=0.0003x+2.7614 | | F=7/5(n-7) | | 2x+(-4)=y | | 7-4x+3=1x-16-3x |